Bed bug (Cimex lectularius) infestation in a surgery ward from northeastern Brazil - Brasil Gadelha Farias, Luís Arthur; Campos Lima Gonçalves , Tainá Catarina; Santana Girão, Evelyne; Teixeira , Maria Jânia; Moura Santos, Fabrício Kássio; de Oliveira Silva, Maria Isabel Eloy; Carvalhedo Fragoso, Luciana Vládia; Vieira Perdigão Neto , Lauro; Nobre Rodrigues , Jorge Luiz (Revista de Patologia Tropical / Journal of Tropical Pathology, 2024)
Bed bugs are arthropods of public health significance that have experienced a global resurgence. In this context, we are reporting a bed bug infestation in a surgical ward in Brazil. Thirteen patients in the surgical ward were identified as having diffuse erythematous maculopapular lesions of unknown origin. Similar signs and symptoms were observed among healthcare professionals in the same unit. The issue was addressed with all relevant departments, and a multifaceted approach was adopted to manage the infestation. Bed bugs may potentially pose health risks to both patients and healthcare professionals. It is imperative to actively monitor the structural integrity of the hospital’s physical facilities to prevent arthropod infestations. KEY WORDS: Bed bugs; Cimex lectularius; ectoparasitic infestations; hospitals.